Age and APOE affect L-carnitine system metabolites in the brain in the APOE-TR model - Huguenard, Claire J. C.; Cseresznye, Adam; Darcey, Teresa; Nkiliza, Aurore; Evans, James E.; Hazen, Stanley L.; Mullan, Michael; Crawford, Fiona; Abdullah, Laila (Frontiers in Aging Neuroscience, 2023)
With age, the apolipoprotein E (APOE) E4 allele contributes to the perturbation of the L-carnitine system in Alzheimer’s disease (AD). We therefore hypothesized that in aging mice, APOE genotype would affect the L-carnitine system in the brain and the periphery. Levels of L-carnitine, L-carnitine metabolites (including γ-butyrobetaine (GBB) and crotonobetaine) as well as acylcarnitines were evaluated at 10-, 25-, and 50-weeks, in the brain and periphery, in a targeted replacement mouse model of human APOE (APOE-TR). Aged APOE-TR mice were also administered 125 mg/kg of L-carnitine orally daily for seven days followed by evaluation of brain, liver and plasma L-carnitine, L-carnitine metabolites and acylcarnitines using hydrophilic interaction liquid chromatography (HILIC) with high-resolution mass spectrometers. Compared to E4-TR, an age-dependent increase among E2- and E3-TR mice was detected for medium- and long-chain acylcarnitines (MCA and LCA, respectively) within the cerebrovasculature. In the parenchyma, compared to E3-TR, both E2- and E4-TR had age-dependent increases in MCA and LCA. Following L-carnitine oral challenge, E4-TR mice had higher increases in the L-carnitine metabolites, GBB and crotonobetaine, in the brain and a reduction of plasma to brain total acylcarnitines ratios compared to other genotypes. These studies suggest that with aging, the presence of the E4 allele may contribute to alterations in the L-carnitine bioenergetics system and also contributes to the generation of L-carnitine metabolites that could have detrimental effects on the vascular system. Collectively the E4 allele and aging may therefore contribute to AD pathogenesis through aging-related lipid bioenergetics and cerebrovascular dysfunctions.